Policy Perspectives on the Mid-Day Meal Scheme (PM POSHAN) in Elementary Schools in Darjeeling, West Bengal (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The Mid-day meal is one of the major tools in enhancing child nutrition, school attendance and educational outcomes in across India. However, in Darjeeling district, the scheme faces the unique challenges which include dispersed settlements, difficult terrain, infrastructural gaps, the presence of tea-garden communities, and significant ethno linguistic diversity. This study analyzes multiple policy perspectives applied to PM POSHAN/MDM in Darjeeling’s elementary schools, specifically focusing on the rights-based lens, nutritional and health perspective, educational incentive perspective, governance viewpoint, equity perspective, and operational challenges. Based on the analysis of administrative data, the paper also proposes the targeted strategies or policy recommendation specific to Darjeeling district.